Pemetaan Daerah Rawan Bencana Tanah Longsor di Wilayah Kecamatan Silo Kabupaten Jember - Jaduk Arief Susetyo; Sri Astutik; Fahmi Arif Kurnianto; Elan Artono Nurdin; Era Iswara Pangastuti (School of Postgraduate Studies, Diponegoro Univer, 2023)
Silo District, Jember Regency is an area with a mountainous topography dominated by relatively steep slopes. Many landslides occurred in the Silo District area. Based on the results of observations, in 2022 to July there have been 8 landslides in the Silo District area. Landslide disasters can be minimized by mapping landslide-prone areas. The mapping method used is a weighted overlay method for each parameter. The landslide parameters used in this study are: parameters of soil depth, rainfall, slope, soil type and land use. The final results of data processing for each parameter in this study will produce a map of landslide-prone areas in Silo District, Jember Regency. . Based on the research results, the landslide vulnerability classes are grouped into four classifications, namely low, medium, high and very high. The results showed that the Silo District was an area with high vulnerability (54%), medium vulnerability (37%), very high vulnerability (9%) and low vulnerability (1%). Mulyorejo Village is the village with the widest very high vulnerability classification in Silo District.